Polyurea resin composition

The polyurea resin composition, characterized by its specific polyisocyanate and polyamine compound composition, addresses the issues of long curing times and inadequate protective properties in existing polyurea resin compositions, resulting in improved productivity and protective performance for molded body coatings.

JP2025067854APending Publication Date: 2025-04-24UNITIKA LTD

Patent Information

Application Number
JP2024176381
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-12
Filing Date
2024-10-08
Publication Date
2025-04-24

AI Technical Summary

Technical Problem

Existing polyurea resin compositions used as coatings for molded bodies have long curing times, which hinder productivity, and lack sufficient water resistance and chemical resistance to withstand stringent protective requirements.

Method used

A polyurea resin composition comprising a polyisocyanate compound with at least 51% by mass of aliphatic polyisocyanate or its derivative, primarily in biuret or nurate forms, and a polyamine compound with 80% or more of aspartic acid ester compounds, including at least 30% by mass of non-alicyclic aspartic acid ester compounds.

Benefits of technology

The composition achieves a faster curing time, improved adhesion, and enhanced water resistance and chemical resistance, making it suitable for coatings on molded bodies while maintaining transparency and weather resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025067854000001
    Figure 2025067854000001
  • Figure 2025067854000002
    Figure 2025067854000002
Patent Text Reader

Abstract

To provide a polyurea resin composition which has an excellent curing time, is also excellent in water resistance and chemical resistance when formed into a coating film, and has suitable adhesion and hardness as a coating paint of a molding.SOLUTION: The polyurea resin composition contains a polyisocyanate compound (A) and a polyamine compound (B). The polyisocyanate compound (A) contains 51 mass% or more of an aliphatic polyisocyanate compound or its derivative (A1). The aliphatic polyisocyanate compound or its derivative (A1) contains more than 80 mass% in total of biurets or nurates. The polyamine compound (B) contains 80 mass% or more of an aspartic acid ester compound (B1). The aspartic acid ester compound (B1) contains 30 mass% or more of a non-alicyclic aspartic acid ester compound (B2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyurea resin composition and a laminate using the same. [Background technology]

[0002] Polyurea resins, which are made from polyisocyanate compounds and polyamine compounds, have excellent physical properties, can be used without solvents, and have excellent water resistance, so they are used as reinforcing materials for aging buildings and frameworks, and as materials that impart durability to natural disasters such as earthquakes.

[0003] On the other hand, coating paints for molded resins are required to have water resistance, chemical resistance, hardness, etc., in order to protect the molded body. While the above-mentioned characteristics of polyurea resins are desirable for coating paints, general polyisocyanate compounds and polyamine compounds react extremely quickly, and when the two components are mixed, they harden within a few seconds. For this reason, polyurea resins are generally applied over a large area to flat surfaces using a special device called an impingement mixing type sprayer, which is unsuitable for application to molded bodies with complex shapes and curved surfaces.

[0004] Among polyurea resins, those using aspartic acid ester compounds have been developed that have a guaranteed pot life and can be applied manually using a brush, trowel, roller, or the like. For example, a polyurea resin composition disclosed in Patent Document 1, which is made of a polyisocyanate compound of a specific structure and an aspartic acid ester compound and has a viscosity in a specific range, has the characteristics of a good pot life and excellent appearance and chemical resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2022-66853 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the polyurea resin composition disclosed in Patent Document 1 takes a long time to cure, and there is room for further improvement in order to improve productivity. Furthermore, from the viewpoint of protecting molded articles, water resistance and chemical resistance capable of withstanding harsher conditions are required.

[0007] In view of the above circumstances, an object of the present invention is to provide a polyurethane resin composition which is excellent in curing time, has excellent water resistance and chemical resistance when formed into a coating film, and has adhesion and hardness suitable for use as a coating material for a molded article. [Means for solving the problem]

[0008] The present inventors have found that the above problems can be solved by using a polyisocyanate compound (A) and an aspartic acid ester compound (B) having specific types and structures, and have completed the present invention. That is, the gist of the present invention is as follows.

[0009] [1] A polyurea resin composition containing a polyisocyanate compound (A) and a polyamine compound (B), The polyisocyanate compound (A) contains 51 mass% or more of an aliphatic polyisocyanate compound or a derivative thereof (A1), The aliphatic polyisocyanate compound or its derivative (A1) contains more than 80 mass% of biuret or nurate in total, The polyamine compound (B) contains 80 mass% or more of an aspartic acid ester compound (B1), A polyurea resin composition, characterized in that the aspartic acid ester compound (B1) contains 30 mass % or more of a non-alicyclic aspartic acid ester compound (B2). [2] The polyisocyanate compound (A) contains 85 mass% or more of an aliphatic polyisocyanate compound or a derivative thereof (A1), The polyamine compound (B) contains 95% by mass or more of an aspartic acid ester compound (B1), The polyurea resin composition according to [1], wherein the aspartic acid ester compound (B1) contains 55 mass % or more of a non-alicyclic aspartic acid ester compound (B2). [3] The polyurea resin composition according to [1] or [2], wherein the aspartic acid ester compound (B1) is a compound represented by the following general formula (1): X(-NH-CH(CHCOOR 1 )COOR 2 ) n (1) (X is any organic group having 5 to 30 carbon atoms, n is an integer of 2 or more, R 1 and R 2 are each independently an alkyl group having 1 to 20 carbon atoms. [4] The polyurea resin composition according to any one of [1] to [3], wherein the NCO% of the compound constituting the polyisocyanate compound (A) is 15% or more. [5] The polyurea resin composition according to any one of [1] to [4], which does not contain an alcohol compound. [6] The polyurea resin composition according to any one of [1] to [5], which has a tack-free time of less than 60 minutes. [7] A laminate comprising a layer made of the polyurea resin composition according to any one of [1] to [6] above and a layer made of a thermoplastic plastic, wherein the layer made of the polyurea resin composition is formed by any one of the group consisting of brush coating, trowel coating, cartridge gun coating, casting, and in-mold coating. [8] The laminate according to [7], wherein the thermoplastic is any one of the group consisting of ABS, polyolefin, polyamide, and polyester. [9] The laminate according to [7] or [8], wherein the haze of the layer made of the polyurea resin composition at a thickness of 1 mm is 30% or less.

[10] A casting resin, characterized by using the polyurea resin composition according to any one of [1] to [6] above.

[11] A resin for coating inside a mold, characterized by using the polyurea resin composition according to any one of [1] to [6] above. Effect of the Invention

[0010] The polyurea resin composition of the present invention is solvent-free and yet has a good curing time, enabling improvement in productivity. In addition, it has good adhesion to molded articles and is excellent in water resistance, chemical resistance, and hardness. Moreover, the polyurea resin composition of the present invention can be made excellent in transparency and weather resistance by selecting the types of the polyisocyanate compound (A), the polyamine compound (B) and the additives. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The polyurea resin composition of the present invention contains a polyisocyanate compound (A) and a polyamine compound (B).

[0012] <Polyisocyanate compound (A)> The polyisocyanate compound (A) constituting the polyurea resin composition of the present invention is a compound having two or more isocyanate groups in one molecule, and may be in the form of a monomer, oligomer, or polymer. In addition, it may be modified with a chain extender such as a polyol component.

[0013] The polyisocyanate compound (A) in the present invention must contain 51 mass% or more of an aliphatic polyisocyanate compound or its derivative (A1), preferably 60 mass% or more, more preferably 75 mass% or more, even more preferably 80 mass% or more, and most preferably 85 mass% or more. By having the content of the aliphatic polyisocyanate compound or its derivative (A1) in the polyisocyanate compound (A) of 51 mass% or more, the transparency of the resulting coating film is improved, and the adhesion to the molding resin is also improved.

[0014] Examples of the aliphatic polyisocyanate compound include 1,6-hexamethylene diisocyanate (HDI), 1,4-tetramethylene diisocyanate, 1,5-pentamethylene diisocyanate, 2-methylpentane-1,5-diisocyanate, 3-methylpentane-1,5-diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, 2,6-diisocyanate methyl caproate, lysine diisocyanate, trioxyethylene diisocyanate, isophorone diisocyanate, 1,4 -bis(isocyanatomethyl)cyclohexane, 4,4'-methylenebis(cyclohexyl isocyanate), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,3-bis(isocyanatoethyl)cyclohexane, 1,4-bis(isocyanatoethyl)cyclohexane, 2,5- or 2,6-bis(isocyanatomethyl)norbornane (NBDI), and hydrogenated aromatic polyisocyanates. Among these, 1,6-hexamethylene diisocyanate (HDI) is preferred as the aliphatic polyisocyanate compound from the viewpoints of curing time and adhesion to molding resins.

[0015] Examples of the derivatives of the aliphatic polyisocyanate compound include isocyanate-terminated prepolymers obtained by reacting an aliphatic polyisocyanate compound with a polyamine or a polyol, allophanate bodies, urea bodies, carbodiimide bodies, biuret bodies, uretdione bodies, and nurate bodies, as well as those modified into water-dispersible types, with biuret bodies and nurate bodies being preferred, and nurate bodies being more preferred. In the present invention, the aliphatic polyisocyanate compound or its derivative (A1) must have a total content of biuret and nurate forms exceeding 80 mass%, preferably 85 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more. When the aliphatic polyisocyanate compound or derivative thereof (A1) contains a predetermined amount or more of a biuret form and a nurate form, the curing speed is increased, and the resulting coating film has improved properties such as hardness and chemical resistance. The above-mentioned derivatives of the aliphatic polyisocyanate compound can be obtained by a known method. Depending on the method for producing the nurate compound, a small amount of excess reactant (e.g., pentamers, heptamers, etc.) may be contained as a by-product, but in the present invention, these are also considered as nurate compounds.

[0016] The polyisocyanate compound (A) may contain, in addition to the aliphatic polyisocyanate compound or its derivative (A1), other isocyanate compounds (A2) according to the desired performance such as physical properties, pot life, etc. Examples of such isocyanate compounds include aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and 1,5-naphthylene diisocyanate. Among these, when HDI is used as the aliphatic polyisocyanate compound, the isocyanate components other than HDI are preferably 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, diphenylmethane diisocyanate (MDI), xylylene diisocyanate, and 1,5-naphthylene diisocyanate from the viewpoint of compatibility with HDI, and more preferably 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, and diphenylmethane diisocyanate. Two or more of these may be used in combination. Also usable are isocyanate-terminated prepolymers, allophanate forms, urea forms, carbodiimide forms, biuret forms, uretdione forms, nurate forms, and those modified into water-dispersible forms.

[0017] From the viewpoints of curing time and adhesion to molding resin, the content of the other isocyanate compound (A2) must be 49 mass % or less of the polyisocyanate compound (A), preferably 40 mass % or less, more preferably 25 mass % or less, even more preferably 20 mass % or less, and most preferably 10 mass % or less.

[0018] The isocyanate group content (NCO%) in the polyisocyanate compound (A) is preferably 5 to 50%, more preferably 10 to 45%, and further preferably 15 to 30%. A polyurea resin composition containing a polyisocyanate compound (A) having an isocyanate group content below the above range may not obtain sufficient hardness. When the polyisocyanate compound (A) is composed of two or more kinds of compounds, it is more preferable that the isocyanate group content (NCO%) of each compound is 15% or more.

[0019] The viscosity of the polyisocyanate compound (A) at 25° C. is preferably 500 to 30,000 mPa·s, more preferably 1,000 to 25,000 mPa·s, and even more preferably 1,500 to 20,000 mPa·s. A coating material made of a resin composition containing a polyisocyanate compound (A) having a viscosity of more than 30,000 mPa·s at 25° C. may take a long time to mix uniformly with other materials or may be difficult to apply uniformly, while a coating material having a viscosity of less than 500 mPa·s may not achieve a sufficient thickness.

[0020] <Polyamine Compound (B)> The polyamine compound (B) constituting the polyurea resin composition of the present invention must contain 80 mass% or more of the aspartic acid ester compound (B1), preferably 85 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more. If the content of the aspartic acid ester compound (B1) is less than 80 mass%, the resulting cured product may have poor adhesion and chemical resistance.

[0021] The aspartic acid ester compound (B1) is preferably a compound represented by the following general formula (1) from the viewpoints of curing speed and adhesion to a molded article. X(-NH-CH(CHCOOR 1 )COOR 2 ) n (1) (X is any organic group having 5 to 30 carbon atoms, n is an integer of 2 or more, R 1 and R 2 are each independently an alkyl group having 1 to 20 carbon atoms. Among them, R 1 and R 2 Each of these has more preferably 1 to 10 carbon atoms, and particularly preferably 1 to 5. If the number of carbon atoms is more than 20, the resulting coating film may not have sufficient hardness.

[0022] Furthermore, the aspartic acid ester compound (B1) must contain 30% by mass or more of a non-alicyclic aspartic acid ester compound (B2) that does not contain an alicyclic structure in its chemical structure, preferably 40% by mass or more, more preferably 55% by mass or more, and even more preferably 70% by mass or more. If the content of the non-alicyclic aspartic acid ester compound (B2) is less than 30% by mass, the resulting coating film may take a long time to dry, resulting in reduced productivity.

[0023] The method for producing the aspartic acid ester compound is not limited, and any known method can be used.

[0024] The amine value of the aspartic acid ester compound is preferably from 50 to 1000 mgKOH / g, more preferably from 100 to 700 mgKOH / g, and further preferably from 150 to 500 mgKOH / g. If the amine value of the aspartic acid ester compound is less than 50 mgKOH / g, the resin composition may not have a sufficient curing rate, and if it exceeds 1000 mgKOH / g, the resulting coating film may have reduced adhesion to the molded article.

[0025] Commercially available non-alicyclic aspartic acid ester compounds (B2) include, for example, "Feispartic F220" and "Desmophen NH1220", and examples of aspartic acid ester compounds (B3) containing an alicyclic structure in their chemical structure include, for example, "Desmophen NH1420", "Desmophen NH1520", "Feispartic F420", and "Feispartic F520".

[0026] The polyurea resin composition of the present invention may contain a polyamine compound (B4) other than the aspartic acid ester compound (B1) within a range that does not impair the effects of the present invention. Other polyamine compounds (B4) include aromatic amine compounds such as 4,4'-diamino-3,3'-dichlorodiphenylmethane and diethyltoluenediamine, polyetheramine compounds such as O,O'-bis(2-aminopropyl)propylene glycol and polyalkylene oxide-di-p-aminobenzoate, and aliphatic amine compounds such as hexamethylenediamine, nonanediamine, and reactants of epoxy compounds and primary amines. As the other polyamine compounds, either primary amines or secondary amines can be used.

[0027] <Other ingredients (C)> The polyurea resin composition of the present invention may contain other components within the range not impairing the effects of the present invention. Specific examples include polyol, polyester resin, epoxy resin, silicone resin, urethane resin, polyolefin resin, terpene resin, styrene resin, acrylic resin, etc.

[0028] Examples of polyols include dihydric alkyl alcohols such as ethylene glycol, propylene glycol, and 1,6-hexanediol, trihydric alkyl alcohols such as glycerin, and tetrahydric or higher alkyl alcohols such as diglycerin, erythritol, and sorbitol. Examples of polymeric compounds include oligomers or polymers (wherein the terminal monomer component is an aliphatic alcohol) such as polyester polyols, polyether polyols, acrylic polyols, polyolefin polyols, polyurethane polyols, and alkylene oxide adducts of amines. Among these, from the viewpoint of adhesion and hardness of the resulting coating film, divalent or higher alkyl alcohols, polyether polyols, polyolefin polyols, polyurethane polyols, polyester polyols, and alkylene oxide adducts of amines are preferred, with polyether polyols and polyester polyols being particularly preferred.

[0029] The number average molecular weight of the polyol is not particularly limited, but is preferably 200 to 5,000, more preferably 400 to 4,000, and even more preferably 500 to 3,000. If the number average molecular weight of the polyol compound (C) is less than 200, the adhesion to the molded article may decrease, and if the number average molecular weight exceeds 5,000, the hardness of the coating film may decrease.

[0030] The total content of the other polyamine compound (B4) and the other component (C) is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the total content of the polyamine compound (B) and the other component (C). If the total content of (B4) and (C) exceeds 20% by mass, the resulting coating film may have poor adhesion to the molded article and poor transparency.

[0031] <Polyurea resin composition> In the resin composition of the present invention, the equivalent ratio is calculated by the following formula. (Amount of isocyanate groups (mol) of polyisocyanate compound (A)) ÷ (Amount of amino groups (mol) of polyamine compound (B) + Amount of hydroxyl groups (mol) of other components) The equivalent ratio is preferably 0.7 to 1.3, more preferably 0.8 to 1.2, and particularly preferably 0.9 to 1.1. Outside this range, the resulting coating film may suffer from poor curing, swelling, or foaming.

[0032] The tack-free time of the polyurea resin composition of the present invention is preferably less than 60 minutes, more preferably 15 seconds to 30 minutes, even more preferably 30 seconds to 20 minutes, and particularly preferably 1 minute to 15 minutes. If the tack-free time is less than 15 seconds, the coating material may harden before it is sufficiently applied to the adherend, and if it exceeds 60 minutes, productivity may decrease. The tack-dry time refers to the time required for the coating film to dry without leaving fingerprints or paint on the finger when the coating film is lightly touched with a finger.

[0033] The curing time of the polyurea resin composition of the present invention is preferably 60 to 1440 minutes, more preferably 70 to 960 minutes, and particularly preferably 80 to 720 minutes. If the curing time is less than 60 minutes, the substrate may be damaged by reaction heat, and if it exceeds 1440 minutes, the productivity may decrease. In the present invention, the curing time refers to the time required for the consumption rate of isocyanate groups to reach 80% as determined by IR spectroscopy.

[0034] The polyurea resin composition of the present invention may contain a catalyst in order to improve the physical properties of the resulting coating film and to adjust the pot life and curing temperature. Specific examples of catalysts include tertiary amines such as triethylamine, tributylamine, triethylenediamine, 2-dimethylaminoethyl ether, diazabicycloundecene, and N-methylmorpholine; metal catalysts such as dibutyltin diacetate, dibutyltin laurate, 3-diacetoxytetrabutylstannoxane, tin octenate, tin chloride, tin butyl trichloride, bismuth trichloride, bismuth octenate, tetrakis(2-ethylhexyl)titanate, tetrabutoxytitanium, and metal salts of acetoacetic acid; and quaternary ammonium salts.

[0035] The polyurea resin composition of the present invention may contain additives as necessary. Examples of additives include silica, basic inorganic compounds, pH adjusters, metal oxide fine particles, tackifiers, waxes, ultraviolet absorbers, light stabilizers, surface conditioners such as leveling agents and wetting agents, defoamers, anti-popping agents, anti-sagging agents, paint spread improvers, thixotropy-imparting agents, colorants such as pigments and dyes, dispersants, diluents, fillers, release agents, etc. The resin composition may contain two or more types of additives, and each additive may be composed of a single substance or two or more types of substances. The above additives can also be added in advance to the polyisocyanate compound (A) or the polyamine compound (B). The amount of the additive to be added can be appropriately determined depending on the purpose.

[0036] Examples of basic inorganic compounds include hydroxides, oxides, and (hydrogen)carbonates of alkali metals or alkaline earth metals, such as calcium hydroxide, sodium hydroxide, magnesium hydroxide, calcium oxide, calcium carbonate, sodium carbonate, and sodium hydrogen carbonate. Among these, hydroxides of alkali metals or alkaline earth metals are more preferable from the viewpoint of their effect on stability and viscosity.

[0037] Examples of the pH adjuster include organic acid salts of alkali metals or alkaline earth metals, such as calcium acetate, sodium acetate, potassium acetate, calcium formate, sodium formate, potassium formate, calcium propionate, sodium propionate, and potassium propionate.

[0038] Examples of metal oxide fine particles include titanium oxide, magnesium oxide, ferrous oxide, ferric oxide, triiron tetroxide, aluminum oxide, vanadium oxide, and copper oxide.

[0039] Examples of tackifiers include polysaccharides such as xanthan gum and guar gum, rosin resins and derivatives thereof, terpene resins and derivatives thereof, aliphatic resins and derivatives thereof, and aromatic resins and derivatives thereof.

[0040] Examples of waxes include paraffin wax, amide wax, olefin wax, olefin oxide wax, montan wax, and copolymer wax.

[0041] Examples of the ultraviolet absorbing agent include hindered amine-based, cinnamic acid-based, benzophenone-based, triazine-based, and triazole-based agents.

[0042] Examples of light stabilizers include those in which the amine in the hindered amine is a secondary NH type, a tertiary NCH3 type, NR type, NOR type, and the like. In addition, the hindered amine light stabilizer may have a structure other than an alkyl group, such as an ester group, an acrylic group, an imide group, a formyl group, a carbonate group, or an ether group in the main skeleton, and those of any molecular weight can be used. The light stabilizer can be used in combination with the above-mentioned ultraviolet absorber, and the combination is not limited.

[0043] Examples of the surface conditioner include silicone-based, acrylic polymer-based, vinyl-based, acetylene-based, fluorine-based, and alkylene oxide-based.

[0044] Examples of the defoaming agent include mineral oil-based, amide-based, metal soap-based, silicone-based, higher alcohols and derivatives thereof, fatty acid derivatives, polyolefin-based, etc. Among these, polyolefin-based agents are more preferred from the viewpoints of defoaming properties and chemical resistance.

[0045] Examples of the thixotropy-imparting agent include acrylic polymers, organic urea compounds and modified products thereof, fumed silica, bentonite, organic clay, layered silicate, etc. Among them, from the viewpoint of the effect relative to the amount added, organic urea compounds and modified products thereof are more preferred.

[0046] As the coloring agent, any of inorganic pigments, organic pigments, and dyes can be used. Examples of inorganic pigments include red clay, yellow clay, green clay, graphite, Prussian blue, zinc oxide, cobalt blue, viridian, and titanium white. Examples of organic pigments include alkali blue, lysol red, disazo yellow, phthalocyanine blue, quinacridone red, and isoindoline yellow. Examples of dyes include madder, sappan, and indigo.

[0047] Examples of the dispersant include acrylic polymers, polycarboxylic acid compounds, phosphonic acid compounds, sulfonic acid compounds and neutralized compounds thereof, quaternary ammonium salt compounds, amide compounds, and polyether compounds.

[0048] As the diluent, any common organic solvent can be used so long as it is not reactive with the polyisocyanate compound (A). Examples of organic solvents that can be used as diluents include hydrocarbon compounds such as toluene, xylene, and cyclohexane, carbonyl compounds such as acetone, 2-butanone, and isophorone, and ester compounds such as ethyl acetate and butyl acetate. These may be used alone or in combination of two or more. The content of the organic solvent in the polyurea resin composition is preferably 10% by mass or less. If the content of the organic solvent exceeds 10% by mass, not only the physical properties of the resulting coating film may be deteriorated, but also the inherent advantage of the polyurea resin, that is, the ability to be produced without a solvent, may be lost.

[0049] Examples of the filler include inorganic compounds such as calcium carbonate and calcium hydroxide, inorganic minerals such as talc, kaolin, apatite and layered silicate, glass beads, glass fibers, silica, etc. Among these, talc, glass beads and silica are preferred from the viewpoints of the amount added and viscosity.

[0050] Examples of the release agent include silicone-based, fluorine-based, fluorine-containing silicone-based, amide-based, olefin-based, urethane-based, oil-based, wax-based, and ester-based agents.

[0051] <Application> The polyurea resin composition of the present invention can be used as a paint such as a primer, intermediate coat or top coat, a sizing agent, a reinforcing material, or the like for materials such as metals such as iron plates and steel plates, plastics, films, sheets, ceramics, glass, concrete, fibers, and paper. Examples of the plastic material include layers made of thermoplastic plastics such as ABS, polyolefin, polyamide, and polyester, and a laminate can be obtained by forming a layer made of a polyurea resin composition. The polyurea resin composition of the present invention can be suitably used to impart aesthetic appearance, weather resistance, water resistance, chemical resistance, rust resistance, abrasion resistance, adhesion, and the like to the above-mentioned materials. In particular, since it has a good curing speed, it can be used as a protective coating for molded articles, a casting resin, or an in-mold coating resin.

[0052] Any known coating method can be used, and specific examples include immersion (dip coat, dipping), brushing, troweling, cartridge gun, static mixer, spray, casting (pouring into a mold), and in-mold coating.

[0053] The curing temperature can be appropriately determined in consideration of workability and productivity, but is preferably 40 to 100°C, more preferably 40 to 80°C, and particularly preferably 40 to 60°C, from the viewpoints of safety and heat resistance of the substrate.

[0054] The polyurea resin composition of the present invention can be suitably used as anticorrosive / waterproof paint, impact resistance improving paint, protective paint, etc. Examples of applicable uses include piping, pipes, steel pipes, structures (metal, concrete), marine plant facilities, wind power generators, ships, factories, oil refineries, power plants, water treatment facilities (wastewater treatment plants, water purification plants, sewer pipes, water supply pipes, manholes), railway track structures, bridge piers, tunnels, roofs, linings, building materials, robot materials, factory and warehouse floors, parking lots, industrial facilities, refrigeration / distribution warehouses, skating rinks, sports facilities, anti-slip signs, road markings, underground structures, athletic field stands, gymnasium domes, walls, urethane foam, molded objects, wood, plywood, automobile parts, truck beds, polystyrene foam, and stages. EXAMPLES

[0055] The present invention will be explained in more detail with reference to examples and comparative examples, but the present invention is not limited to the following examples in any way. In the examples and comparative examples, the following raw materials were used as they were without purification or distillation.

[0056] <Polyisocyanate compound (A)> A1-1: Nurate-modified hexamethylene diisocyanate (Tosoh's "Coronate HXR", isocyanate group content 21.9NCO%, viscosity 1,700mPa s) A1-2: Biuret-modified hexamethylene diisocyanate (Asahi Chemical Industry Co., Ltd. "Duranate 24A-100", isocyanate group content 23.5NCO%, viscosity 1,800mPa s) A1-3: Nurate-modified pentamethylene diisocyanate ("STABIO D-370" manufactured by Mitsui Chemicals, Inc., isocyanate group content 25.0NCO%, viscosity 2,000mPa·s) A1-4: 1,6-hexamethylene diisocyanate (Tokyo Chemical Industry Co., Ltd., isocyanate group content 49.9NCO%, viscosity 4mPa s) A1-5: Isocyanate-terminated HDI prepolymer synthesized by the following method A four-neck flask equipped with a stirrer, thermometer, reflux condenser, nitrogen inlet tube, and dropping funnel was conditioned with nitrogen, and 100 parts by mass of hexamethylene diisocyanate (HDI) and 86 parts by mass of polypropylene glycol (number average molecular weight 750) were charged. The temperature inside the reactor was kept at 95°C for 90 minutes with stirring to carry out a urethane reaction. The cooled reaction liquid was filtered, and unreacted HDI was removed using a thin-film evaporator. An isocyanate-terminated HDI prepolymer with an isocyanate group content of 5.0 NCO%, a viscosity at 25°C of 3,000 mPa.s, and a number average molecular weight of 1,600 was obtained. A1-6: Adduct-modified hexamethylene diisocyanate (Asahi Chemical Industry Co., Ltd. "Duranate AE700-100", isocyanate group content 11.9NCO%, viscosity 800mPa s) A2-1: Polymeric MDI (Tosoh Corporation's "Millionate MR-200", isocyanate group content 30.9NCO%, viscosity 160mPa·s) A2-2: Carbodiimide-modified MDI (Tosoh Corporation's "Millionate MTL", isocyanate group content 28.9NCO%, viscosity 40mPa·s)

[0057] <Polyamine Compound (B)> (B2) Non-alicyclic: Aspartic acid ester compounds that do not contain an alicyclic structure in their chemical structure B2: Aspartic acid ester compound (Feiyang Co., Ltd. "Feispartic F220", CAS No. 168253-59-6, N,N'-[2-methyl-1,5-pentanediyl]bis(diethyl aspartate), amine value 241 mgKOH / g, viscosity 80 mPa s)

[0058] (B3) Alicyclic: Aspartic acid ester compounds containing an alicyclic structure in their chemical structure B3-1: Aspartic acid ester compound (Feiyang "Feispartic F420", CAS No. 136210-30-5, N,N'-[methylenebis(4,1-cyclohexanediyl)]bis(diethyl aspartate), amine value 203 mgKOH / g, viscosity 1,450 mPa s) B3-2: Aspartic acid ester compound (Feiyang "Feispartic F520", CAS No. 136210-32-7, N,N'-[methylenebis(2-methyl-4,1-cyclohexanediyl)]bis(diethyl aspartate), amine value 190 mgKOH / g, viscosity 1,400 mPa s)

[0059] (B4) Aspartic acid ester compounds (B2) and (B3) and other polyamine compounds B4: Diethyltoluenediamine (Kumiai Chemical Co., Ltd. "Heartcure 10", amine value 630 mgKOH / g, viscosity 300 mPa·s)

[0060] <Other ingredients (C)> C1: Glycerin / propylene oxide adduct (ADEKA "G700", hydroxyl value 224 mg KOH / g, viscosity 260 mPa s)

[0061] <Additives (D)> D1: UV absorber (BASF triazine compound "TINUVIN405") D2: Light stabilizer (BASF hindered amine compound "TINUVIN152") D3: Defoamer (Mitsui Chemicals liquid polyolefin "Lucant LX010") D4: Release agent (BYK unsaturated ester release agent "BYK-P 9912")

[0062] The substrates used in the adhesion evaluation are as follows: ABS: Acrylonitrile-butadiene-styrene copolymer (Standard Test Piece) PA6: Polyamide 6 (Standard Test Piece) PET: Polyethylene terephthalate (Engineering Test Services) PP: Polypropylene (Standard Test Piece) The dimensions of the substrates are all 2 mm thick x 50 mm x 50 mm.

[0063] Various physical properties were measured by the following evaluation methods. (1) Isocyanate group content (NCO%) It was determined according to the hydrochloric acid back titration method of di-n-butylamine of JIS K 7301.

[0064] (2) Amine value The value was calculated according to the indicator titration method of JIS K 7237.

[0065] (3) Hydroxyl value The value was calculated according to the indicator titration method of JIS K 1557-1:2007.

[0066] (4) NCO / active hydrogen equivalent ratio The concentration of each functional group (mmol / g) was determined from the amount of each component in the resin composition, the isocyanate group content (NCO%), the amine value, and the hydroxyl value of each component determined in (1) to (3) above, and the NCO / active hydrogen equivalent ratio was calculated using the following formula. (Isocyanate group concentration) ÷ [(Amino group concentration) + (Hydroxy group concentration)]

[0067] (5) Viscosity The rotational viscosity (mPa·s) at 25°C was measured using a Brookfield Dial Viscometer (BROOKFIELD ENGINEERING LABORATORIES, INC., Brookfield Dial Viscometer Model LVT).

[0068] (6) Dry time to touch Based on JIS K 5600, the tactile drying time was determined as the time from when the polyisocyanate compound (A) and the polyamine compound (B) were mixed until the fingertip was lightly touched to the center of the coating surface and no longer stained. Dry to touch time can be used as an indicator of productivity. The tack-free time was evaluated according to the following criteria. ◎◎: Dry to touch time is more than 1 minute 30 seconds and less than 10 minutes ◎: Dry to the touch time is more than 1 minute and less than 1 minute 30 seconds, or more than 10 minutes and less than 15 minutes ○: Dry to the touch time is more than 30 seconds and less than 1 minute, or more than 15 minutes and less than 25 minutes △: Dry to the touch time is more than 15 seconds and less than 30 seconds, or more than 25 minutes and less than 30 minutes ×: Dry to touch time is 15 seconds or less or more than 30 minutes For practical purposes, a rating of 2 or higher is necessary.

[0069] (7)Curing time Using a Thermo Fisher FT-IR, -1 The NCO consumption rate was calculated from the calibration curve of the nearby NCO peak, and the time it took for this to reach 80% was taken as the curing time. Spectral resolution: 2 cm -1 The measurement was performed with 16 cumulative measurements.

[0070] (8) Adhesion The adhesion was evaluated by an adhesion strength test based on JIS A 6909. The polyurea resin composition was applied to the substrates shown in Tables 1 and 2 in a coating thickness of 1 mm, and cured at 25° C. for 24 hours. A tensile jig (40 mm square) was fixed to the coating film using an epoxy adhesive, and the adhesion strength was measured using an adhesion tester (Technotester RT-1000LDII manufactured by Sanko Techno Co., Ltd.). Adhesion to ABS, PA6, and PET was evaluated according to the following criteria. ◎◎: 2.0N / mm 2 End ◎: 1.5N / mm 2 More than 2.0N / mm 2 less than ○: 1.0N / mm 2 More than 1.5N / mm 2 less than △: 0.7N / mm 2 More than 1.0N / mm 2 less than ×:0.7N / mm 2 less than The adhesion to PP was evaluated according to the following criteria. ◎◎: 1.0N / mm 2 End ◎:0·9N / mm 2 More than 1.0N / mm 2 less than ○: 0.8N / mm 2 More than 0.9N / mm 2 less than △: 0.7N / mm 2 More than 0.8N / mm 2 less than ×:0.7N / mm 2 less than In practice, adhesion to ABS, PA6, PET, and PP is 0.7N / mm 2 The above is necessary.

[0071] (9) Water, acid and alkali resistance The polyurea resin composition was poured into a metal mold so that the thickness was 2 mm and both sides were 2 cm, and cured for 24 hours at 25° C. The obtained cured product was immersed in distilled water, 10% sulfuric acid, and 10% aqueous sodium hydroxide solution, respectively, and stored at 60° C. for 4 hours. After immersion, the test pieces were dried at 150°C for 2 hours, and the dissolution rate was calculated using the following formula and evaluated according to the following criteria. Dissolution rate (%) = [(weight of test piece before test) - (weight of test piece after test)] ÷ (weight of test piece before test)] × 100 The elution rates in distilled water, 10% sulfuric acid, and 10% aqueous sodium hydroxide solution can be used as indicators of water resistance, chemical resistance (acid resistance), and chemical resistance (alkali resistance), respectively. The dissolution rate was evaluated according to the following criteria. ◎◎: Dissolution rate less than 3% ◎: Dissolution rate is 3% or more, less than 5% ○: Dissolution rate is 5% or more and less than 10% △: Dissolution rate 10% or more, less than 15% ×: Elution rate 15% or more For practical purposes, a rating of 2 or higher is necessary.

[0072] (10)Hardness The polyurea resin composition was poured into a metal mold so that the thickness was 2 mm and both sides were 2 cm, and cured for 24 hours at 25° C. The Shore hardness of the obtained cured product was measured using a Type D durometer Shore hardness tester (GS-619 manufactured by Techclock Corporation) based on JIS K 6253. For practical purposes, a hardness rating of 40 or higher is required. ◎◎:Hardness 60 or more ◎: Hardness 50 or more, less than 60 ○: Hardness 45 or more, less than 50 △: Hardness 40 or more, less than 45 ×: Hardness less than 40

[0073] (11) Transparency The polyurea resin composition was poured into a metal mold to a thickness of 1 mm and cured for 24 hours at 25° C. The haze value of the resulting cured product was determined using a turbidity meter (NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd.) based on JIS K7361. The haze value was evaluated according to the following criteria. 5: Less than 15% 4: More than 15% and less than 20% 3: More than 20% and less than 25% 2: More than 25% and less than 30% 1:More than 30%.

[0074] (11) Weather resistance The polyurethane resin composition was applied to a 2 mm thick ABS resin plate with a brush so that the thickness was 1 mm. After aging for 24 hours at 25°C, the surface gloss of the resulting laminate was measured using a xenon weather meter (Atlas Ci4400 manufactured by Toyo Seiki Seisakusho Co., Ltd.) under the following test conditions. (Test conditions) Light source: Xenon arc lamp Radiation intensity: 180W / m 2 Black panel temperature: 60℃ Rainfall cycle: 18 minutes out of 120 minutes Test time: 500 hours Humidity: 50% The weather resistance was evaluated based on the rate of change in surface gloss (60°) before and after the test, according to the following criteria. 5: Change in surface gloss is less than 5% 4: Change in surface gloss is 5% or more but less than 10% 3: The change in surface gloss is 10% or more but less than 15% 2: The change in surface gloss is 15% or more but less than 20% 1: The change in surface gloss is 20% or more, or cracks occur in the polyurea coating.

[0075] (12) Overall rating The results of all evaluations regarding productivity (touch-free time), adhesion, water resistance, chemical resistance (acid resistance, alkali resistance), and hardness, which are the main effects of the present invention, were evaluated comprehensively. More specifically, the lowest evaluation result among all these evaluation results was used as the result of the comprehensive evaluation.

[0076] Example 1 In a 50mL glass vial, 16.4g of B2 as the polyamine compound (B) and 13.6g of A1-1 as the polyisocyanate compound (A) were added and quickly mixed with a metal spoon. This mixture was used to create a cured product or a laminate according to the description in the above physical property evaluation, and various evaluations were performed. The evaluation results are shown in Table 1.

[0077] Examples 2 to 14, Comparative Examples 2 to 4, 6 to 7 The evaluation was carried out in the same manner as in Example 1, except that the polyisocyanate compound (A), polyamine compound (B), other component (C), and additive (D) were changed to the types and ratios shown in Tables 1 and 2. The evaluation results are shown in Tables 1 and 2. In Examples 4 and 5, and Comparative Example 3, the viscosities of the polyisocyanate compound (A) prepared by mixing (A1) were 800 mPa s, 2,500 mPa s, and 460 mPa s, respectively.

[0078] Comparative Example 1 The same procedure as in Example 1 was carried out except that the polyisocyanate compound (A) was not used, but no cured product could be obtained.

[0079] Comparative Example 5 The same procedure as in Example 1 was carried out except that the polyamine compound (B) was not used, but no cured product was obtained.

[0080] The configurations and properties of the polyurea resin compositions of the examples and comparative examples are shown in Tables 1 and 2.

[0081] [Table 1]

[0082] [Table 2]

[0083] As shown in Tables 1 and 2, the polyurea resin composition of the present invention contains a polyisocyanate compound and an aspartic acid ester compound having a specific structure, and therefore has an excellent curing time and excellent water resistance and chemical resistance when formed into a coating film, making it suitable as a coating material for molded articles.

[0084] In Comparative Examples 2 and 3, the content of the biuret or nurate form in the polyisocyanate compound (A) was low, and therefore the obtained cured products were inferior in one or more of hardness, alkali resistance, and adhesion. In Comparative Example 4, since the content of the aliphatic polyisocyanate compound or its derivative (A1) in the polyisocyanate compound (A) was small, the obtained cured product was poor in adhesion and also poor in transparency. In Comparative Example 6, the content of the aspartic acid ester compound (B1) in the polyamine compound (B) was low, so that the obtained cured product had poor adhesion and was also poor in water resistance and alkali resistance. In Comparative Example 7, since the content of the non-alicyclic aspartic acid ester compound (B2) in the aspartic acid ester compound (B1) was small, the tack-dry time of the polyurea resin composition was long, and the productivity was poor.

Claims

1. A polyurea resin composition containing a polyisocyanate compound (A) and a polyamine compound (B), The polyisocyanate compound (A) contains 51 mass% or more of an aliphatic polyisocyanate compound or a derivative thereof (A1), The aliphatic polyisocyanate compound or its derivative (A1) contains more than 80 mass% of biuret or nurate in total, The polyamine compound (B) contains 80% by mass or more of an aspartic acid ester compound (B1), A polyurea resin composition, characterized in that the aspartic acid ester compound (B1) contains 30 mass % or more of a non-alicyclic aspartic acid ester compound (B2).

2. The polyisocyanate compound (A) contains 85 mass% or more of an aliphatic polyisocyanate compound or a derivative thereof (A1), The polyamine compound (B) contains 95% by mass or more of an aspartic acid ester compound (B1), 2. The polyurea resin composition according to claim 1, wherein the aspartic acid ester compound (B1) contains 55 mass % or more of a non-alicyclic aspartic acid ester compound (B2).

3. 3. The polyurea resin composition according to claim 1, wherein the aspartic acid ester compound (B1) is a compound represented by the following general formula (1): X(-NH-CH(CH 2 P. 1 )COOR 2 ) n (1) (X is any organic group having 5 to 30 carbon atoms, n is an integer of 2 or more, R 1 and R 2 are each independently an alkyl group having 1 to 20 carbon atoms.

4. 3. The polyurea resin composition according to claim 1, wherein the NCO % of the compound constituting the polyisocyanate compound (A) is 15% or more.

5. 3. The polyurea resin composition according to claim 1, which does not contain an alcohol compound.

6. 3. The polyurea resin composition according to claim 1, wherein the tack-free time is less than 60 minutes.

7. A laminate comprising a layer made of the polyurea resin composition according to claim 1 and a layer made of a thermoplastic plastic, wherein the layer made of the polyurea resin composition is formed by any one of the group consisting of brush coating, trowel coating, cartridge gun coating, casting, and in-mold coating.

8. 8. The laminate according to claim 7, wherein the thermoplastic is any one of the group consisting of ABS, polyolefin, polyamide, and polyester.

9. 9. The laminate according to claim 7, wherein the layer made of the polyurea resin composition has a haze of 30% or less at a thickness of 1 mm.

10. A casting resin comprising the polyurea resin composition according to claim 1 or 2.

11. A resin for coating inside a mold, comprising the polyurea resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Polyaspartic coating composition, coated film and coating article

    JP2022066853A

Cited By

  • Curable resin composition

    JP7883041B1